Effects of a spore-forming probiotic blend on bowel habits and physical well-being in adults with functional constipation: A randomized, double-blind, placebo-controlled trial - Hyung Gyu Park; Han Bin Lee; Minjee Lee; Haeseong Park; Minji Kang; Minkyung Bok; Yeongtaek Hwang; Kyuho Jeong; Sungho Maeng; Hyunjung Lim; Jin Seok Moon (PLoS ONE, 2026)
We aimed to evaluate the efficacy and safety of a spore-forming probiotic blend containing Clostridium butyricum IDCC 1301, Weizmannia coagulans IDCC 1201, and Bacillus subtilis IDCC 1101 for improving bowel function and well-being in adults with functional constipation (FC). In a randomized, double-blind, placebo-controlled trial, 78 adults with FC (Rome IV criteria) received either probiotic blend (n = 40) or placebo (n = 38) daily for 4 weeks. Primary outcomes were changes in weekly spontaneous bowel movements (WSBM) and stool form. Secondary outcomes included physical functioning scores from the 36-Item Short Form Health Survey. The probiotic blend group showed significant improvements in irritant bowel movements (p = 0.0458), incomplete evacuation (p = 0.0374), and abdominal pain before defecation (p = 0.0090). Stool consistency shifted toward normal types (Bristol types 3–4, p = 0.0176). Physical functioning improved only in the probiotic blend group (p = 0.0300). Probiotic blend effectively alleviated symptoms of FC and improved physical well-being. Trial registration: Clinical Research Information Service (CRIS), KCT0010085.